On-Task and Off-Task Self-Assessment: Which Works Better on Young Learners’ Writing Performance? - Ni Luh Putu Eka Sulistia Dewi; I Nyoman Pradnyana Bayu Trisna (Jurnal Pendidikan dan Pengajaran, 2021)
The implementation of self-assessment might contribute to the young learners’ English proficiency and affective domain. Yet, there is still limited findings found for the effect on young learners’ writing performance. This experimental study investigated the effect of on-task and off-task self-assessment on young learners of English as a foreign language in Bali, Indonesia. 46 sixth graders participated in this study were required to do self-assessment in completing their writing prompt. A self-assessment checklist was used as the instrument. The on-task self-assessment group applies the self-assessment checklist at every stage of their writing process, namely pre-writing, drafting, revising, editing, and publishing.  On the other hand, the off-task self-assessment group uses the self-assessment checklist before they start the writing process. Using independent samples t-test for hypothesis testing, it was found that there is no significant difference in both groups’ writing performance since the real probability that is due to sampling error is .194 which is bigger than the significance level of .05. Therefore, self-assessment could be implemented in on-task and off-task since it brings similar effect to the young learners’ writing performance.